Consistency as a desirable and achievable objective in the proposed rewrite of the South African Income Tax Act, 1962 (Act No. 58 of 1962) - Franzsen, R.C.D. (Riel) (University of Pretoria, 2013)
Dissertation (MPhil)--University of Pretoria, 2011.